LESSON PRESENTATION MELALUI TEKS UNTUK MENINGKATKAN KETERAMPILAN MENGAJAR GURU - Heri Susanto (Center of Language and Cultural Studies, 2016)
This paper describes lesson presentation to improve teachers’ skills in classroom interactions. Lesson presentation or teaching to transfer is skills a teaher should demonstrate to enhance and convince students on a concept. It helps students identify material context, guides students to summarize, and broadens thinking skills through reflection and teacher giude. This paper argues in Indonesian language teaching, lesson presentation improves if teachers implement text structures in a variety of genres. The way teachers are formally trapped into teacher-centered that teacher talks dominate will be minimized using lesson presentation of appropriate contexts. Presentation should be temporary, at the beginning, at the core, or at the closing encouraging fluency in appropriate exposures. Equipped with compsite texts, lesson presentation signifies beneficials for teaching skills.